Need to exercise conventionality control after recent labour transformations - Teodoro, Maria Cecília Máximo; de Andrade, Iris Soier do Nascimento; Andrade, Karin Bhering (Revista Chilena de Derecho del Trabajo y de la Seguridad Social, 2020)
It is the purpose of this work to try to review and explain some of the recent changes, recently, introduced into the Brazilian labor law frame work, and brought by the Federal Law number 13.467, dated July 13, 2017, which has been the foundation of The Labor Reform in Brazil, as well as the Executive Act number 881/2019 (so called the Economic Liberty Executive Act) which was converted into the Federal Law number 13.874, dated September 20, 2019. It has become necessary to read such law changes in the context of international legal frameworks, and check if all of them went through the check and balances of conventionality control and review. This way, it is one of the goals of this work to understand what a conventionality control is, and if the above mentioned recent changes in the Brazilian Labor Law have complied with international declarations and conventions, as well as addressing possible solutions